Social Media and Mental Health: Understanding the Association between SNS Addiction and Depression in Students - Lakho, Afsheen; Ain, Noor-ul-; Memon, Kainat; Lakhiar, Aakash; Kalsoom, Ume-; Siyal, Fahad Jibran; Jiskani, Shahzad Ali; Jokhio, Faiza; Lund, Nadeem; Abbas, Waseem; Khoso, Mir Hassan; Shaikh, Bakhtawar (Indus Journal of Bioscience Research, 2025)
Background: Social media usage has significantly increased among university students, leading to concerns regarding its psychological impact. Excessive engagement with social networking sites (SNS) has been associated with depression, social comparison, and sleep disturbances. However, limited research has explored these associations in developing regions like Pakistan. Objective: This study aims to examine the relationship between social media addiction and depression among university students in Larkana, Sindh, Pakistan. Materials and Methods: A cross-sectional study was conducted among 289 undergraduate and postgraduate students. Data were collected through a structured questionnaire incorporating the Bergen Social Media Addiction Scale (BSMAS) and the Patient Health Questionnaire-9 (PHQ-9) to assess social media addiction and depressive symptoms, respectively. Pearson’s correlation and multiple regression analyses were performed using SPSS v24.0 to evaluate association between SNS addiction and depression, controlling for demographic and lifestyle factors. A p-value of <0.05 was considered as statistically significant. Results: The findings revealed a significant positive correlation (p<0.001) between social media addiction and depression, with higher SNS addiction scores associated with greater depressive symptoms. Gender differences were observed, with female students reporting slightly higher levels of social media addition than males (p<0.05). Additionally, excessive SNS use was linked to sleep disruption, reduced academic performance, and increased psychological distress. Conclusion: This study provides empirical evidence supporting the association between social media addiction and depression among university students. The findings emphasize the need for digital literacy programs, psychosocial interventions, and institutional policies to regulate screen time and mitigate the negative effects of SNS addiction. Future research should adopt longitudinal and cross-sectional approaches to explore causality and underlying socio-economic factors influencing this relationship.